Comparison of UV Index and Total Ozone Column of Aura/OMI and Ground Measurement from Nepal Himalayas - Sharma, Rishi R; Kjeldstad, Berit; Bhattarai, Binod K (Journal of the Institute of Engineering, 2012)
Ground UV index and total ozone measured from four stations of Nepal Himalaya using NILU UV Multiband Filter Radiometer (MBFR) were compared with that of the Aura/OMI satellite products using the data from October 2008 to December 2010. The main goal of the validation was to find how the satellite products deviate with that of ground measurement in the mountainous sites where the stations have unique set of geographical and environmental conditions. The altitudes of the stations vary from 72 m to 2850 m in a short span of horizontal distance. The comparison was done for clear-sky and cloudy-sky condition using Cloud Transmission Factor (CLT) as a proxy. It was found that UV indices estimated by the satellite have higher values compared to ground instrument. The relative difference (bias) of the four stations are varied from 34.5 ± 24.0% to 47.9 ± 17.4% for cloud free condition and from 106.4 ± 81.44 % to 286.4 ± 254.8% for cloudy condition. The correlation coefficients are more than 0.8 for cloud free condition. The total ozone column comparison showed the mean relative difference (bias) range from -2.17 ± 3.52% to 2.97 ± 3.92% under cloud free condition and -4.42 ± 5.64% to 1.36 ± 6.14% under cloudy condition. The possible factors for this discrepancy are discussed and some important factors are highlighted. DOI: http://dx.doi.org/10.3126/jie.v8i3.5938 JIE 2011; 8(3): 114-129